The Effect of Chloride Acid Concentration and Demineralization Time on Gelatin Characteristic of EEL Fish Bones (Anguilla marmorata (Q.) Gaimard) - Jamaluddin,; Angriani Abdullah ,; Yonelian Yuyun, (Journal of Pharmacy and Nutrition Sciences, 2019)
Anguilla marmorata (Q.) Gaimard, eel bonefish is one of the potentials sources for gelatin manufacture. This study aims to determine the concentration of hydrochloric acid (3%; 4%) and to optimize demineralization time (12 hours; 24 hours) for thequality of gelatin. Characteristic of gelatin was determined by analysis of water content, ash content and protein content. To optimize gelatin extraction from eel fish bone, Mann Whitney test with 4 – factor was adopted. Spectrophotometer FTIR was used to analyze functional groups of gelatin. Values of water content, ash and protein content of each combination of acid chloride and demineralization time have met the requirements. The spectrum of FTIR showed a typical gelatin functional group. The best combination of treatment is at 3% hydrochloric acid concentration and 12 hours of demineralization time.